2015
DOI: 10.1002/bdm.1925
|View full text |Cite
|
Sign up to set email alerts
|

The (In)visibility of Psychodiagnosticians' Expertise

Abstract: This study investigates decision making in mental health care. Specifically, it compares the diagnostic decision outcomes (i.e., the quality of diagnoses) and the diagnostic decision process (i.e., pre‐decisional information acquisition patterns) of novice and experienced clinical psychologists. Participants' eye movements were recorded while they completed diagnostic tasks, classifying mental disorders. In line with previous research, our findings indicate that diagnosticians' performance is not related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In medicine, all perceptual-cognitive tasks involved detection of pathology or abnormality from XR-scans (e.g., Donovan & Litchfield, 2013), CT-scans (e.g., Bertram et al, 2016), PET/CT-scans (Gegenfurtner, Lehtinen, Jarodzka, & Säljö, 2017), lesion images (e.g., Dreiseitl, Pivec, & Binder, 2012), video clips (e.g., Balslev et al, 2012), MRI scans (Crowe, Gilchrist, & Kent, 2018), electrocardiogram (Wood, Batt, Appelboam, Harris, & Wilson, 2014), or monitoring during an anesthesia procedure (Grundgeiger, Klöffel, Mohme, Wurmb, & Happel, 2017). In all studies that included a detection task, except two (Schulte-Mecklenbeck, Spaanjaars, & Witteman, 2017; Wood et al, 2013), participants were either instructed to provide a report of their diagnosis or indicate with a mouse click the location of a possible pathology or abnormality, but no explicit instructions were given on the accuracy or speed of execution. Therefore, tasks in all these studies were classified as nonexplicit tasks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In medicine, all perceptual-cognitive tasks involved detection of pathology or abnormality from XR-scans (e.g., Donovan & Litchfield, 2013), CT-scans (e.g., Bertram et al, 2016), PET/CT-scans (Gegenfurtner, Lehtinen, Jarodzka, & Säljö, 2017), lesion images (e.g., Dreiseitl, Pivec, & Binder, 2012), video clips (e.g., Balslev et al, 2012), MRI scans (Crowe, Gilchrist, & Kent, 2018), electrocardiogram (Wood, Batt, Appelboam, Harris, & Wilson, 2014), or monitoring during an anesthesia procedure (Grundgeiger, Klöffel, Mohme, Wurmb, & Happel, 2017). In all studies that included a detection task, except two (Schulte-Mecklenbeck, Spaanjaars, & Witteman, 2017; Wood et al, 2013), participants were either instructed to provide a report of their diagnosis or indicate with a mouse click the location of a possible pathology or abnormality, but no explicit instructions were given on the accuracy or speed of execution. Therefore, tasks in all these studies were classified as nonexplicit tasks.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, tasks in all these studies were classified as nonexplicit tasks. Only in two studies did participants receive specific instructions concerning speed and accuracy; these tasks were categorized as maximizing-optimizing tasks (Schulte-Mecklenbeck et al, 2017; Wood et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While it is self-evident that clinical psychologists who have worked longer in the field gain more experience, it has also been shown that they do not necessarily gain more expertise in psychodiagnostic decision-making (Spengler et al, 2009;Vollmer et al, 2013): Even after years of experience, clinical psychologists are relatively poor at categorizing mental disorders into DSM categories (Brailey et al, 2001;Schulte-Mecklenbeck et al, 2015) and make judgments strikingly similar to those of novices (e.g., AEgisdóttir et al, 2006;Garb, 1998;Strasser & Gruber, 2004;Witteman & Van den Bercken, 2007).…”
Section: Introductionmentioning
confidence: 99%